The Development of an Adventure Board Game in the Accounting World to Enhance Business Transaction Analysis for Basic Accounting 1 Course of First-Year Vocational Certificate Students (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) develop an accounting adventure board game in the accounting world to meet the efficiency criterion of 80/80, 2) compare the analytical thinking ability of the students before and after learning by using the adventure board game in the accounting world, and 3) study the students’ satisfaction toward the development of analytical thinking ability in business transactions using an adventure board game in the accounting world. The sample group consisted of 44 first-year vocational certificate students of Eastern Technological College (E. Tech), class BAC 1/5, selected by cluster random sampling. The research instruments were 1) the learning management plan, 2) the accounting adventure board game, 3) the test to measure the ability to analyze business transactions, and 4) the satisfaction questionnaire. Data were analyzed by finding the mean, standard deviation, media efficiency test (E1/E2), and dependent t-test. The research results found that 1) the adventure board game in the accounting world had an efficiency value of E1/E2 equal to 80.22/87.33, which was higher than the efficiency criteria set at 80/80, 2) the students who studied by using adventure board game in the accounting world had an ability to analyze business transactions after studying (Mean = 17.47, S.D. = 2.00) higher than before studying (Mean = 9.93, S.D. = 1.91) with statistical significance at the .05 level and 3) the students had the highest overall satisfaction towards the development of their analytical thinking ability in business transactions using the adventure board game in the accounting world (Mean = 4.53, S.D. = 0.65).